2006
DOI: 10.2979/esj.2006.5.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Using the Troubled Project Recovery Framework: Problem Recognition and Decision to Recover

Abstract: Information system development projects continue to be delivered significantly behind schedule, drastically over budget and without meeting specifications. To improve the likelihood of success for these projects a staged framework for recovery and rehabilitation has been suggested. This framework is composed of four stages that include twelve steps. The four stages are recognition, immediate recovery, sustained recovery and maturity. A study was performed to validate the first stage of the framework, the Recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(15 reference statements)
2
26
0
Order By: Relevance
“…Nevertheless, they stayed outside of focus of project management theory and practice, while only being mentioned indirectly in project management, as it was stated in the Introduction (Nikander, 2002;Haji-Kazemi et al, 2013, 2015. Philip, Schwabe, and Wende (2010) stated that only three major empirical works had studied the concept of early warning in project management: two of which in IT industry (Kappelman et al, 2007;Havelka & Rajkumar, 2006according to Philip et al, 2010 and one in construction industry (Nikander & Eloranta, 2001; according to Philip et al, 2010). On the other hand, Nikander (2002) showed that Ansoff 's idea on the usage of weak signals can be used on projects, so it is reasonable to expect possibility of success in development of the corresponding systematic solution for project managers.…”
Section: Early Warning Systemsmentioning
confidence: 99%
“…Nevertheless, they stayed outside of focus of project management theory and practice, while only being mentioned indirectly in project management, as it was stated in the Introduction (Nikander, 2002;Haji-Kazemi et al, 2013, 2015. Philip, Schwabe, and Wende (2010) stated that only three major empirical works had studied the concept of early warning in project management: two of which in IT industry (Kappelman et al, 2007;Havelka & Rajkumar, 2006according to Philip et al, 2010 and one in construction industry (Nikander & Eloranta, 2001; according to Philip et al, 2010). On the other hand, Nikander (2002) showed that Ansoff 's idea on the usage of weak signals can be used on projects, so it is reasonable to expect possibility of success in development of the corresponding systematic solution for project managers.…”
Section: Early Warning Systemsmentioning
confidence: 99%
“…The development and successful implementation of a new information system (IS) project is a notoriously difficult task. Once begun, IS development projects are very difficult to control (Havelka & Rajkumar, 2006; Iacovou & Dexter, 2004; Keil, Mixon, Saarinen, & Tuunainen, 1994/95). Descriptions of problem projects and outright failures are the basis of legend and have appeared in the popular press for many years (Gibbs, 1994; Gladden, 1982; Kindel, 1992; Varon, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the works that study EWSs over the course of the whole project lifecycle [14,33] The early project stages are critical because the management of EWSs in these stages, provided that corrective actions are taken, would allow the projects to be completed within the original time estimates. In our case study, we analyzed the warning signs that emerged in relation to the usage of IM during the first 20 percent of the project.…”
Section: Early Warning Signsmentioning
confidence: 99%
“…Project troubles experienced before a failure are hardly ever detected early enough in the IT industry [14]. Identifying and managing such troubles is an effective solution that can be utilized to save project efforts and resources, especially in the early project stages.…”
Section: Early Warning Signsmentioning
confidence: 99%
See 1 more Smart Citation